2015
DOI: 10.1021/acsami.5b05715
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis g-C3N4/Nano-InVO4 Nanocomposites and Enhanced Photocatalytic Activity for Hydrogen Production under Visible Light Irradiation

Abstract: We synthesized g-C3N4/nano-InVO4 heterojunction-type photocatalyts by in situ growth of InVO4 nanoparticles onto the surface of g-C3N4 sheets via a hydrothermal process. The results of SEM and TEM showed that the obtained InVO4 nanoparticles 20 nm in size dispersed uniformly on the surface of g-C3N4 sheets, which revealed that g-C3N4 sheets was probably a promising support for in situ growth of nanosize materials. The achieved intimate interface promoted the charge transfer and inhibited the recombination rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 60 publications
(136 reference statements)
3
72
3
Order By: Relevance
“…Compared with the p‐InVO 4 microspheres, the as‐prepared composites have a higher absorption in both the UV‐light region and the visible‐light region, and the absorption edges of CQDs/p‐InVO 4 have a significant redshift. Additionally, the band gaps of the composites are obtained by extrapolating the linear portion of [ α h υ ] 2 versus (h υ ) curves . As depicted in Figure b, the E g (semiconductor bandgap) of the p‐InVO 4 microspheres is estimated to be about 2.21 eV, which is close to that reported in the literature .…”
Section: Resultssupporting
confidence: 73%
“…Compared with the p‐InVO 4 microspheres, the as‐prepared composites have a higher absorption in both the UV‐light region and the visible‐light region, and the absorption edges of CQDs/p‐InVO 4 have a significant redshift. Additionally, the band gaps of the composites are obtained by extrapolating the linear portion of [ α h υ ] 2 versus (h υ ) curves . As depicted in Figure b, the E g (semiconductor bandgap) of the p‐InVO 4 microspheres is estimated to be about 2.21 eV, which is close to that reported in the literature .…”
Section: Resultssupporting
confidence: 73%
“…In the case of the g-C 3 N 4 /CuO nanocomposite, CuO were all nano-sized and well dispersed throughout the micron-sized g-C 3 N 4 . Previous studies have indicated that active sites exposed on the surface of nanocomposite would significantly increase the enhancement well dispersed nano-component concentrations to some extent [49,50]. Thus, g-C 3 N 4 /20 wt % CuO exhibited higher catalytic performance on the thermal decomposition of AP than g-C 3 N 4 /10 wt % CuO and g-C 3 N 4 /5 wt % CuO, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…As far as bare g-C 3 N 4 was concerned, normally, the photogenerated electron-hole pairs quickly recombined and only a fraction of them participated in water splitting reaction, resulting in low photocatalytic activity 5,6,15,21 . Based on the above analysis of the experiment and characterization results, the possible photocatalytic reaction mechanism and electron transfer processes of the g-C 3 N 4 /Ag 2 CrO 4 nanocomposites were proposed (Fig.…”
Section: Resultsmentioning
confidence: 99%